Morphology and morphometry of cattle’s blood in the Ukrainian red-spotted dairy breed - Kolomak, I.; Sakhnenkо S.; Kononenko, D.; Ovcharenko, D. (Scientific Progress & Innovations, 2024)
Hematological studies are an important element reflecting the physiological state of animals. It is carried out for the purpose of making a diagnosis, especially during the latent course of infectious diseases. The calculation of the leukocyte formula is widely used in the diagnosis of infectious pathologies, the latest data indicate a fundamental difference in the ratio of formed blood elements of young and adult individuals, some data reflect interspecies and age differences. The information regarding the reference ranges for the hematological parameters of the formed blood elements of the Ukrainian red-spotted dairy breed is currently partial. Therefore, the purpose of the study was to determine the reference indices of the leukocyte formula and morphometric indices of the blood of cows of the Ukrainian red-spotted dairy breed of two age groups and to compare their values. Hematological studies were carried out on the basis of the Department of Normal and Pathological Anatomy and Physiology of Animals, Poltava State Agrarian University. Blood for the study was collected from cattle of the Ukrainian red-speckled dairy breed of two age groups (young calves up to 3 months of age and cows aged 3 to 5 years), belonging to the Agroecology PE. The study has established that the percentage of lymphocytes in the blood of calves of the Ukrainian black-spotted dairy breed at the age of 3 months, according to the results of the leukogram study, is by 3.56 % higher (Р<0.05) compared to cows at the age of 3 up to 5 years. Along with that, in the blood of cows from 3 to 5 years of age, the percentage of monocytes was higher by 20.3 % (Р<0.05) compared to young calves under the age of 3 months. Morphologically, in the prepared smears, along with physiologically normal erythrocytes and leukocytes in shape and structure, pathological forms were also detected. In particular, pathological forms of erythrocytes were found in the smears. At the same time, such pathological forms of erythrocytes as codocytes and target-like forms of erythrocytes were found in smears made from the blood of calves. Instead, only codocytes were detected in smears made from the blood of cows. The number of codocytes in young animals was greater (from 4, 5 to 9 specimens in the field of view of the microscope) compared to adult animals. It was determined that, metrically, according to the area indices, lymphocytes in young animals were probably larger by 9.01% (Р<0.05) in comparison with adult animals. Instead, monocytes and eosinophils were larger by 15.32 and 1.29 % (Р<0.05) in the group of animals aged 3 to 5 years.